The Analysis of School Readiness Factors in Implementing Teaching Factory (TEFA) in the Department of Mechanical Engineering - Adiyanto, Arnold; Abizar, Haris; Supriyatna, Deddy (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the factors influencing school readiness in implementing the Teaching Factory (TEFA) in the Mechanical Engineering Department of SMKN 2 Serang. The Teaching Factory is a learning model that integrates classroom learning with real industrial work situations, aiming to improve students' competencies and entrepreneurial spirit. This research employs a descriptive method with a quantitative approach. The population consists of all teachers and TEFA managers in the Mechanical Engineering Department of SMKN 2 Serang, totaling 15 people, using a saturated sampling technique. Data were collected through closed-ended questionnaires and analyzed using factor analysis. The results show that seven key factors influence the school's readiness to implement TEFA: management, workshop-laboratory, learning-training patterns, marketing and promotion, product and service development, human resources, and industrial partnerships. These factors are interrelated and must be developed optimally to ensure effective TEFA implementation and maximize its benefits for both students and the school. The study recommends strengthening collaboration with industries, improving teachers' competencies, and developing adequate facilities and infrastructure to support the successful implementation of TEFA.